The Economic Life in QOM during the Abbasid Era (132-656 A.H/ 749-125 C.E): Historical Study - BAHAR, ABDULMUNAF A.; HAMMAD, ALAA (Al-Adab Journal, 2021)
QOM It is one of the main and famous cities in the mountain region. It lies along with an arid salty desert: From the north, it is bordered by the city of Al-Ray, to the south by Qashan, and from the west by Sawa. It was conquered by force by Abu Musa al-Ash’ari after the battle of Nahawand in the year (23 AH / 644 CE). The Arabs, including the Ash’arians, contributed to the emergence and development of the city of Qom after their migration to it. It became an Islamic city after its name was associated with the name of the Temple of Fire that was established in one of its villages. This temple represents the most important religious centers of Zoroastrianism. Qom also had a role in the commercial and economic movement, as its people were interested in agriculture as the main source of their livelihood, so they turned to the establishment of channels and streams for irrigation to benefit from rainwater, as well as groundwater. And they depended on the irrigation of crops on the springs and wells that spread in their villages. When the Ash’ari people lived in this city, they brought with them new crops that were not previously grown there, in addition to their contribution to the industrial movement after the flourishing of industry in it significantly, and its industrial products have become very popular throughout the Islamic State. As for trade, Qom had an important geographical location, so that it has a great role in the trade exchange operations through the existence of a group of internal and external roads that linked it with other cities, in addition to the presence of the hostelries spread on those roads that contributed in the practice of commercial activity in various directions.